Students’ academic achievement for taxation courses – a comparative study / Saunah Zainon, Syahrul Ahmar Ahmad and Siti Masnah Saringat - Zainon, Saunah; Ahmad, Syahrul Ahmar; Saringat, Siti Masnah (UiTM Cawangan Johor, 2018)
Accounting education is a discipline, profession and platform for academicians as educators and researchers to conduct various studies on students’ academic achievement. Various courses offered in the field of accounting, such as financial reporting, management accounting, auditing and taxation. The taxation course is specifically evolving in response to changes in economy, budgets, environment and the needs of the stakeholders. In line with these changes, accounting educators continue to refine the content of the taxation course through curriculum review to reflect the most current and relevant needs of the stakeholders. Taxation courses at under graduate levels basically involve two major streams: individual taxation and corporate taxation. The content delivery of these taxation courses are merely in the form of lectures, tutorials and other means of conveyances such as presentations and assignments. Various ways of teaching delivery methods enable rewarding and exciting teaching and learning environment of the taxation courses, which results in an improvement of the students’ academic achievement. As such, this study asserts to determine if there is any difference in the students’ academic achievement for taxation courses with the two different streams of an individual taxation and corporate taxation for two groups of students. The students’ academic achievement of their final semester of grade point average and the taxation courses grades were extracted from their academic records for data analysis. The independent t-test results found that there is a no significant difference between the two groups of students for an individual taxation course, whilst there is a significant difference for corporate taxation course for the two groups of students.